Knowledge, attitude and practice towards breast self examination among female undergraduate students in School of Health Sciences, USM - Romli, Hazne Azira (Universiti Sains Malaysia, 2015)
Breast Self Examination (BSE) is one of the simple screening test that able to detect abnormality in the breast at early stage. The aim of this study was to investigate the knowledge, attitude and practice towards BSE among female undergraduate students in School of Health Sciences, USM. A cross sectional, descriptive study was conducted in 220 respondents who age 20 and above by using structured self administered questionnaire. The simple random sampling technique was used to select the sample for this study. Statistical analysis was conducted by using the Statistical Package for Social Sciences (SPSS) version 22. Meanwhile, the descriptive analysis had been used to summarize socio demographic data of the respondents. One- way ANOVA and Independent t-test was used to evaluate the significance difference between the study variables and the sociodemographic data (age, education level, ethnicity and family history of breast cancer) with the knowledge, attitude and practice towards BSE. A p - value of equal or less than 0.05 was considered significant. In this study population, there were 181 of respondents (82.3%) had excellent knowledge towards BSE meanwhile majority of them had positive attitude (86.8%) towards BSE. Then, for practice towards BSE, most of the students (54.1%) practiced BSE in their life but not consistently practice where some of them practicing BSE rarely (58.0%) and practice it only when they remember to do it ( 55.9%). Educational level was found to be significantly difference with the attitude towards BSE, with p value <0.001. Then, ethnicity also had been found significantly mean difference with the knowledge and attitude towards BSE where the p value is 0.010 and 0.035 respectively. Same goes to family history of breast cancer where it also shows significant mean difference with the practice towards BSE with p value is 0.034. The two main sources of information regarding BSE are internet (27.8%) and television (15.1%). Forgetfulness (47.3%) was the principal reason given by the respondents for not exercising BSE in their life. This study reflected there was a lack of practicing aspect towards BSE although the respondents had excellent knowledge and positive attitude towards BSE. Most of respondents can perform BSE but might be practiced it incorrectly and taking into account that a lack of knowledge on how to perform BSE was the main reason why they did not examine themselves. Therefore, emphasis should be given on encouraging the respondents to practice BSE especially at earlier stage as well establishing educational programmers to teach the respondents so that BSE may help in the early diagnosis of breast cancer.